2015
DOI: 10.1155/2015/707524
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antiradical and Anti-Inflammatory Activities of Ethyl Acetate and Butanolic Subfractions ofAgelanthus dodoneifolius(DC.) Polhill & Wiens (Loranthaceae) Using Equine Myeloperoxidase and Both PMA-Activated Neutrophils and HL-60 Cells

Abstract: The ethyl acetate and n-butanolic subfractions of Agelanthus dodoneifolius were investigated for their antioxidant and antimyeloperoxidase (MPO) activities. The reactive oxygen species (ROS) generation was assessed by lucigenin-enhanced chemiluminescence (CL) and dichlorofluorescein- (DCF-) induced fluorescence techniques from phorbol myristate acetate- (PMA-) stimulated equine neutrophils and human myeloid cell line HL-60, respectively. In parallel, the effects of the tested subfractions were evaluated on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Gallic acid could reduce ROS levels in SH-SY5Y cells induced by 6-hydrodopamine autoxidation [22]. In addition, gallic acid was tested for ROS production in neutrophils, a main producer of superoxide, in which IC 50 value of 0.40 µg/mL was reported for ROS inhibition in PMA-treated neutrophils cells [23], and ROS significantly reduced by gallic acid were found at concentrations of 50–100 μM in LPS-induced cells [24]. Therefore, our study suggested that gallic acid at low concentrations (0 and 0.50 µM) similarly behaved as ROS stimulators, which occurred with cancer cells, but at high concentration (1.00 µM) gallic acid changed its function to that of an antioxidant.…”
Section: Resultsmentioning
confidence: 99%
“…Gallic acid could reduce ROS levels in SH-SY5Y cells induced by 6-hydrodopamine autoxidation [22]. In addition, gallic acid was tested for ROS production in neutrophils, a main producer of superoxide, in which IC 50 value of 0.40 µg/mL was reported for ROS inhibition in PMA-treated neutrophils cells [23], and ROS significantly reduced by gallic acid were found at concentrations of 50–100 μM in LPS-induced cells [24]. Therefore, our study suggested that gallic acid at low concentrations (0 and 0.50 µM) similarly behaved as ROS stimulators, which occurred with cancer cells, but at high concentration (1.00 µM) gallic acid changed its function to that of an antioxidant.…”
Section: Resultsmentioning
confidence: 99%
“…Human myeloid HL-60 cell line was purchased from American Type Culture Collection (Manassas, USA) and cultured according to the method described by Boly et al [ 32 ]. At the beginning of each assay, (1) the cell count of the suspension was estimated to maintain cellular density of 10 6 cells/mL and (2) cell viability was measured using trypan blue assay to main viability > 95%.…”
Section: Methodsmentioning
confidence: 99%
“…A. dodoneifolius dried and powdered leaves exhibited a significant dose dependent radical scavenging activity with EC50 values of 8.20 ± 0.25 and 13.20 ± 0.37 µg/mL, respectively. It has also been reported that A. dodoneifolius subfractions represent potential sources of natural antioxidants and they are antimyeloperoxidase compounds [22].…”
Section: Dpph Free Radical Scavenging Activitiesmentioning
confidence: 99%